Effects of Protein Hydrolysate Derived from Hempseed By-Products on Growth, Mineral Contents, and Quality of Greenhouse Grown Red Oak Lettuce - Bhornchai Harakotr; Thamonwan Trisiri; Lalita Charoensup; Ornprapa Thepsilvisut; Panumart Rithichai; Patcharaporn Suwor; Yaowapha Jirakiattikul (My University, 2025)
The use of biostimulants derived from protein hydrolysates (PH) is now recognized as an effective strategy to promote sustainable vegetable production. This study aimed to evaluate the effects of the foliar application of PH derived from hempseed press cakes on Red Oak lettuce cultivated under greenhouse conditions. Foliar applications of PH at concentrations ranging from 0% to 7.5% (w/v) were compared with water (control) and a commercial product (Germinate®), applied weekly until 35 days after transplanting (DAT). Growth parameters, including plant height, plant width, leaf number, and leaf length and width, were recorded at 14 DAT and subsequently recorded weekly until harvest. Moreover, the fresh and dry weight, chlorophylls, mineral contents, antioxidants, and their activities in the harvested plants were determined. The results showed the positive effects of the hempseed press cake-derived PH on growth, yield, mineral contents, antioxidants, and antioxidant activities. In particular, the foliar application of PH at a concentration of 7.5% (w/v) is recommended to improve the yield and nutritional values in Red Oak lettuce. This study reports the first detailed research on the use of PH derived from hempseed press cakes for lettuce and may offer a sustainable alternative for vegetable production.
Keywords: Plant Growth Enhancement Techniques